Revolution, transition, memory, and oblivion reflections on constitutional change - Belov, Martin (Edward Elgar Publishing, 2020)
This timely book offers a novel theory of constitutional revolutions, providing a new and engaging framework for critically assessing how revolutions and contra-revolutions, transitional periods and the phenomenon of oblivion influence constitutional change. Contributions by leading scholars in the field explore the relationship between revolutions and constitutional order and disorder, considering in particular the impact of political transitions, situations of emergency, coup d'état and the role of memory and oblivion during times of revolution. Through a series of case studies, the book identifies ways in which these phenomena have, and will, affect the formation and amendment of constitutions in both the short and long term. This includes, most notably, those changes which seem to go against the spirit of constitutionalism. In so doing, it provides important insight into how constitutions and constituent powers deal with the influences of the past. Students and scholars engaged in the study of constitutional law, legal theory, theories of the state, transitions of democracy and the philosophy of law will find this ground-breaking book to be a must read"--